Chinese University EFL Teachers' Perceived Support, Innovation, and Teaching Satisfaction in Online Teaching Environments: The Mediation of Teaching Efficacy - Han, Jiying; Gao, Chao; Yang, Jing (Frontiers in Psychology, 2021)
This study investigated the relationships between university EFL teachers' perceived teaching support, teacher innovation, and teaching satisfaction in online teaching environments, especially the mediating role of teaching efficacy. The results of an online questionnaire survey with 473 university EFL teachers revealed that although online peer support did not directly make any difference to teacher innovation and teaching satisfaction, greater perceived support in the form of teaching resources and teaching autonomy improved university EFL teachers' online teaching satisfaction. Online teaching efficacy significantly mediated the relationships between teaching support and teacher innovation and satisfaction. The results offer significant implications for improving the effectiveness of EFL teaching and promoting university EFL teachers' innovation and satisfaction in online teaching environments.